(untitled) (Global Journal of Human-Social Science, 2017)
The present study focuses on teachers role in promoting mental health of students with emotional difficulties in primary schools The role of teachers in promoting mental health is related to early detection of children at risk for mental health problems School-based counselling interventions can contribute to mental health promotion Teaching socio-emotional skills such as emotion management conflict management problem solving skills can strengthen students socio-emotional competence and enhance their psychological resilience In addition positive interpersonal relationships in school context the quality of teacher-student relationships and teacher-parent relationships are associated with teachers role in promoting mental health Constructive interpersonal relationships can contribute in preventing behaviour problems and enhancing students psychosocial development and adaptation Finally the present study asserts that the role of teachers as mental health promoters can empower the identity of students with emotional difficulties